Optimizing Scalp Cooling: (Ultra)Structural Follicular Characteristic and Restorative Advances - Schaffrin-Nabe D; Josten-Nabe A; Heinze A; Tannapfel A; Schaffrin M; Voigtmann R (Cancer Management and Research, 2025)
Doerthe Schaffrin-Nabe,1 Anke Josten-Nabe,1 Adrian Heinze,2 Andrea Tannapfel,3 Merle Schaffrin,1 Rudolf Voigtmann1 1Praxis für Hämatologie und Onkologie, Bochum, 44799, Germany; 2Noack Statistik GmbH, Bonn, 53119, Germany; 3Ruhr-Universität Bochum, Pathologie, Bochum, 44789, GermanyCorrespondence: Doerthe Schaffrin-Nabe, Email schaffrin-nabe@onkologie-bochum.comBackground: Scalp cooling has emerged as a promising intervention for mitigating chemotherapy-induced alopecia, particularly in patients undergoing anthracycline- and taxane-based regimens typically associated with complete hair loss. Despite a visible hair retention rate of 53%, efficacy varies significantly among individuals, influenced by modifiable factors including general health, hair follicle characteristics, and treatment protocols.Methods: This study evaluated 81 breast cancer patients treated with Epirubicin/Cyclophosphamide followed by weekly Paclitaxel application. Hair preservation was assessed using a cross-section trichometer (Cohen Hair Mass Index [HMI]), light microscopy, and scanning electron microscopy. Key parameters evaluated included pre- and posttherapeutic trichological characteristics such as bulb diameter, shaft diameter, anagen rate, as well as grade of hair shaft damage.Results: A total of 53% of patients retained visible hair post-treatment (HMI ≥ 50). Trichological factors—particularly bulb diameter, shaft diameter, and anagen rate—strongly predicted hair preservation outcomes. Additionally, hair shaft integrity, specifically surface damage grading, emerged as a critical determinant of clinically meaningful hair retention.Conclusion: Scalp cooling’s protective effect extends beyond aesthetics, significantly supporting psychological well-being during cancer treatment. Emerging strategies, including cell cycle modulation, antioxidant-based treatments, offer promising avenues to enhance follicular and shaft resilience. While these require further clinical validation, the findings highlight the potential to improve scalp cooling outcomes and raise the standard of supportive oncologic care.Keywords: scalp cooling, chemotherapy-induced alopecia, hair shaft integrity, trichological parameters, cuticle damage, therapeutic optimization